آرنلڈ جے ٹائن بی کے تہذیبی افکار کی روشنی میں اسلامی تہذیب کے عناصر ترکیبی و خصوصیات کا تجزیاتی مطالعہ: An Analytical Study of the Elements and Characteristics of Islamic Civilization in Light of Arnold J. Toynbee's Civilizational Thoughts - Muhammad Shoaib; Dr. Abdul Qadir Buzdar (International Research Journal of Arabic and Islamic Studies, 2024)
Arnold J. Toynbee is regarded as one of the most significant scholars of the modern era. Hailing from a distinguished family with a long-standing reputation in European intellectual circles, his heritage includes notable figures such as his uncle, Arnold Toynbee, a renowned economist and social reformer. This uncle authored numerous works and rendered invaluable public services, leading to the establishment of a hall in London named in his honor. Another uncle, Paget Toynbee, gained recognition in 1932 for his specialization in Dante's studies and translated "The Divine Comedy." While a family's academic legacy may not inherently validate one's own contributions, for Arnold J. Toynbee, it serves as a point of pride. He has elevated the family's scholarly heritage to new heights through his intellectual prowess. In this analytical study, we explore Toynbee's insights into the components of Islamic civilization and its distinctive features. We delve into how his theories articulate the essential characteristics that define Islamic civilization, emphasizing its adaptability, resilience, and contributions to global culture. By examining these elements through Toynbee's lens, we can gain a deeper understanding of the significance of Islamic civilization in the broader context of world history. This study aims to not only highlight the intrinsic values of Islamic civilization but also to position them within the framework of Toynbee's civilizational analysis.